Comparative study of hydrothermal pretreatment of eucalyptus and oil palm empty fruit bunch for ethanol fermentation - Matsumura, Y. (Japan Petroleum Institute, 2014)
Effective energy production from lignocellulosic biomass is one of the most important research topics to employing biomass as a widely used energy source. Using hydrothermal pretreatment, ethanol can be effectively produced from the lignocellulosic biomass. However, the effects of using different feedstock species on ethanol production have not yet been elucidated. In this study, eucalyptus and oil palm empty fruit bunch were selected for hydrothermal pretreatment, followed by enzymatic hydrolysis and ethanol fermentation in order to compare their reaction characteristics. The effect of hydrothermal pretreatment temperature was studied. Furfural, acetic acid, formic acid, and vanillin were studied in the context of being fermentation inhibitors. Differences in glucose production were observed when different feedstocks were used in the hydrothermal pretreatment step, whereas both inhibitor production and its effect on fermentation were the same regardless of feedstock.